PMMA diffusion plate and manufacturing method thereof

By employing a self-made light diffusing agent and composite polymethyl methacrylate microspheres in an in-mold co-extrusion molding technology in a PMMA diffuser plate, the problem of insufficient haze and transparency of the diffuser plate was solved, achieving a light scattering effect with high haze and high transparency, and improving the color performance of the LED backlight.

CN119270398APending Publication Date: 2025-01-07CHANGZHOU AOZHI POLYMER GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411358812.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing technologies have insufficient haze and transparency of diffuser plates, making it difficult to meet the requirements of high color gamut LED backlights.

Method used

The PMMA diffusion plate structure adopts two diffusion layers and a middle quantum dot layer. The diffusion layer contains a self-made light diffusing agent and composite polymethyl methacrylate, and the quantum dot layer contains green perovskite quantum dots. It is manufactured by in-mold co-extrusion molding. The self-made light diffusing agent is grafted onto the surface of nano zinc selenide with polystyrene, and polymethyl methacrylate microspheres are added to the composite polymethyl methacrylate for scattering.

Benefits of technology

It significantly improves the haze and transparency of the diffuser, enhances the light scattering effect, and improves the color performance of the display screen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a PMMA diffusion plate and a manufacturing method thereof, and relates to the technical field of diffusion plate materials, the PMMA diffusion plate comprises an upper diffusion layer, a lower diffusion layer and a middle quantum dot layer, and the upper diffusion layer, the lower diffusion layer and the middle quantum dot layer are manufactured through in-mold three-layer co-extrusion molding; the diffusion layer comprises a self-made light diffusion agent and composite polymethyl methacrylate, the self-made light diffusion agent is prepared by grafting polystyrene on the surface of nano zinc selenide, and the high haze of the diffusion layer is effectively improved; the composite polymethyl methacrylate comprises polymethyl methacrylate and polymethyl methacrylate microspheres, and can be scattered together with the self-made light diffusion agent, so that the high haze of the diffusion layer is further improved, the viscosity of the polymethyl methacrylate is reduced, the flowability is improved, and the transparency of the PMMA diffusion plate is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gypsum board preparation, in particular to a PMMA diffusion plate and a manufacturing method thereof. Background Art

[0002] The diffusion plate uses the continuous refraction, reflection and scattering of light between chemical particles and resin. While covering the light source and the dazzling light source, it can make the light source emit uniform, soft and beautiful light, achieving a comfortable effect of light transmission and opacity. Compared with the traditional CCFL backlight source, LED backlight has many advantages such as high color gamut, high brightness, long life, energy saving and environmental protection, and real-time color control. The high color gamut LED backlight makes the screens of electronic products such as TVs, mobile phones, and tablets that use it have more vivid colors and higher color reproduction. In order to make the display color more perfect, richer in color and closer to the color of the real world, R&D personnel have been committed to finding ways to increase the color gamut value of LED backlight display screens.

[0003] The invention patent with announcement number CN114895492A discloses a quantum dot diffusion plate, including a chain dot layer, an upper surface and a lower surface covered with a protective layer, which has a high brightness effect, thereby reducing the overall cost of the backlight module, but the haze and transparency of the diffusion plate still need to be improved. Therefore, the present invention studies and manufactures a PMMA diffusion plate with high haze and high transparency. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a PMMA diffusion plate with high haze and high transparency.

[0005] A technical solution proposed by the present invention to solve the above technical problems is: a PMMA diffusion plate, comprising two diffusion layers, an upper diffusion layer and a quantum dot layer in the middle; the diffusion layer comprises the following components in mass percentage: 6-12% of a homemade light diffuser, and the rest is composite polymethyl methacrylate; the quantum dot layer comprises the following components in mass percentage: 1-4% of green light perovskite, 1-5% of a homemade light diffuser, and the rest is polymethyl methacrylate; the green perovskite is a green quantum dot with a particle size of 2-3 nm.

[0006] Preferably, the self-made light diffuser is prepared by grafting polystyrene on the surface of nano zinc selenide.

[0007] Preferably, the nano zinc selenide has a triangular morphology and is prepared by the reaction of zinc nitrate, selenium powder, ethylene glycol and sodium hydroxide.

[0008] Preferably, the composite polymethyl methacrylate includes polymethyl methacrylate and polymethyl methacrylate microspheres; the polymethyl methacrylate microspheres are prepared by crosslinking and precipitation polymerization of branched polymethyl methacrylate and polyacrylic acid.

[0009] Preferably, the thickness of the PMMA diffusion plate is 1.6-1.8 mm; the thickness of the diffusion layer is 5.0-7.0% of the thickness of the PMMA diffusion plate.

[0010] Preferably, the method for preparing the PMMA diffuser plate comprises the following specific steps: The homemade light diffuser and composite polymethyl methacrylate in the diffusion layer, the green light perovskite, composite homemade light diffuser and polymethyl methacrylate in the quantum dot layer are prepared according to mass percentage, and are formed into diffusion layer sheet layers, quantum dot layer sheet layers and diffusion layer sheet layers which are laminated and composited together in sequence through in-mold co-extrusion molding. The extrusion speed is 2.8~3.8m / min to obtain a PP diffuser plate.

[0011] Preferably, the preparation method of the homemade light diffuser is: mix nano zinc selenide and sulfuric acid with a mass fraction of 60-64% in a mass ratio of 1-2:20, heat to 43-45°C, react at 400-800rpm for 50-80min, add an equal volume of deionized water and centrifuge, add 2-bromoisobutyryl bromide with a mass of 1-4 times that of nano zinc selenide, triethylamine with a mass of 4-6 times that of nano zinc selenide, and N,N-dimethylformamide with a mass of 4-6 times that of nano zinc selenide, and heat to 68-72°C. , react for 24 hours, then add cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine, the mass ratio of nano zinc selenide, cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine is 1:0.2~0.4:4:6:0.5~0.7:0.02~0.08, raise the temperature to 100~110℃, react for 24 hours, and prepare a homemade light diffuser.

[0012] Preferably, the preparation method of the nano zinc selenide is: mix sodium hydroxide, ethylene glycol and deionized water in equal amounts, stir evenly, add zinc nitrate 0.2 to 0.4 times the mass of sodium hydroxide and selenium powder 0.2 to 0.4 times the mass of sodium hydroxide, stir and react at 200 to 400 rpm for 50 to 70 minutes, transfer to a high-pressure reactor, seal the high-pressure reactor and place it in a drying oven at 170 to 190° C., keep warm for 20 to 24 hours, cool to room temperature, wash 3 to 5 times with an ethanol solution with a mass fraction of 40 to 60%, and finally wash and dry at 60 to 70° C., and finally anneal at a temperature of 650 to 850° C. for 3 to 5 hours, grind, and obtain nano zinc selenide.

[0013] Preferably, the preparation method of the composite polymethyl methacrylate is: xylene and branched polymethyl methacrylate are mixed in a mass ratio of 1:1-1.2, stirred evenly and then heated to 75-85°C, kept warm for 50-80 minutes, and then acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile are added, the mass ratio of xylene, acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile is 1:0.5-0.6:0.5-0.6:0.3:0.02, sealed and heated to 75-85°C, kept warm for reaction for 5-8 hours, transferred to a rotary evaporator, heated in a boiling water bath and evacuated to obtain the composite polymethyl methacrylate.

[0014] Preferably, the preparation method of the branched polymethyl methacrylate is: methyl methacrylate, azobisisoheptanenitrile, sodium iodide and diethylene glycol dimethyl ether are mixed in a mass ratio of 10:0.4:0.1~0.2:10~12, stirred evenly, sealed, frozen at -40~-50°C for 8~12h, vacuumed, thawed naturally, replaced the oxygen in the system with an argon flow and sealed, transferred to an oil bath at 75~85°C, added with 0.1~0.2 times the mass of methyl methacrylate p-chloromethylstyrene, reacted for 6~8h, dissolved with tetrahydrofuran, precipitated with anhydrous ethanol, and dried to obtain branched polymethyl methacrylate.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The PMMA diffusion plate of the present invention comprises two diffusion layers, an upper diffusion layer and a quantum dot layer in the middle, which are manufactured by three-layer co-extrusion molding in a mold, and the diffusion layer comprises a self-made light diffuser and composite polymethyl methacrylate; The self-made light diffuser is prepared by grafting polystyrene on the surface of nano zinc selenide; the nano zinc selenide with triangular morphology has sulfate groups introduced on the surface, so that the surface of the nano zinc selenide has a large amount of negative charge, and then polystyrene is grafted on the surface, so that the self-made light diffuser can be evenly dispersed in the composite polymethyl methacrylate for scattering, thereby effectively improving the high haze of the diffusion layer; The composite polymethyl methacrylate includes polymethyl methacrylate and polymethyl methacrylate microspheres; the polymethyl methacrylate microspheres are prepared by crosslinking and precipitation polymerization of branched polymethyl methacrylate and polyacrylic acid. The polymethyl methacrylate is dissolved in xylene, and then a polymerization monomer acrylic acid, a crosslinking agent pentaerythritol triallyl ether, and an initiator azobisisobutyl cyanide are added, and the precipitation polymerization reaction is initiated by heating to prepare the polymethyl methacrylate composite microspheres. The polymethyl methacrylate microspheres are added to the polymethyl methacrylate, which can be scattered together with a self-made light diffuser, thereby further improving the high haze of the diffusion layer, while reducing the viscosity of the polymethyl methacrylate, increasing the fluidity, and ensuring the transparency of the PMMA diffusion plate. DETAILED DESCRIPTION

[0016] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention. Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art.

[0017] The method for preparing the green perovskite (CH3NH3PbBr3 quantum dots) used in the present invention is prepared by referring to the method of Example 3 in application number CN104861958 A.

[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the PMMA diffusion plates prepared in the examples and comparative examples as follows: Haze: The PMMA diffuser plates manufactured in the examples and comparative examples were tested for haze using NDH-5000.

[0019] Transparency: The PMMA diffuser plates manufactured in the examples and comparative examples were tested for light transmittance by WGT-S. Example 1

[0020] In this embodiment, the diffusion layer includes the following components in percentage by mass: 6% of a homemade light diffuser and the rest of the composite polymethyl methacrylate; the thickness of the diffusion layer is 5.0% of the thickness of the PMMA diffusion plate; In this embodiment, the quantum dot layer includes the following components in percentage by mass: 1% green light perovskite, 1% homemade light diffuser, and the rest is polymethyl methacrylate; the green perovskite is a green quantum dot with a particle size of 2 nm; In this embodiment, the PMMA diffuser plate has a thickness of 1.6 mm and is manufactured by: (1) Mix sodium hydroxide, ethylene glycol and deionized water in equal amounts, stir evenly, add zinc nitrate (0.2 times the mass of sodium hydroxide) and selenium powder (0.2 times the mass of sodium hydroxide), stir at 200 rpm for 50 min, transfer to a high-pressure reactor, seal the high-pressure reactor and place it in a drying oven at 170°C, keep warm for 20 h, cool to room temperature, wash three times with 40% ethanol solution, and finally dry at 60°C. Finally, anneal at 650°C for 3 h, grind, and obtain nano zinc selenide. (2) Mix nano zinc selenide and 60% sulfuric acid in a mass ratio of 1:20, heat to 43°C, react at 400 rpm for 50 min, add an equal volume of deionized water and centrifuge, add 2-bromoisobutyryl bromide (1 times the mass of nano zinc selenide), triethylamine (4 times the mass of nano zinc selenide) and N,N-dimethylformamide (4 times the mass of nano zinc selenide), heat to 68°C, react for 24 h, then add cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine, the mass ratio of nano zinc selenide, cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine is 1:0.2:4:6:0.5:0.02, heat to 100°C, react for 24 h, and prepare a homemade light diffuser; (3) Methyl methacrylate, azobisisoheptanenitrile, sodium iodide and diethylene glycol dimethyl ether were mixed in a mass ratio of 10:0.4:0.1:10, stirred evenly, sealed, and frozen at -40°C for 8 hours, then vacuumed and thawed naturally, the oxygen in the system was replaced by an argon flow, and then sealed, transferred to an oil bath at 75°C, and 0.1 times the mass of methyl methacrylate p-chloromethylstyrene was added. After reacting for 6 hours, the mixture was dissolved in tetrahydrofuran and precipitated with anhydrous ethanol, and dried to obtain branched polymethyl methacrylate; (4) Xylene and branched polymethyl methacrylate were mixed in a mass ratio of 1:1, stirred evenly, and then heated to 75°C for 50 minutes, and then acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile were added, and the mass ratio of xylene, acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile was 1:0.5:0.5:0.3:0.02. The mixture was sealed and heated to 75°C, and the reaction was kept for 5 hours. The mixture was transferred to a rotary evaporator, heated in a boiling water bath and evacuated to obtain a composite polymethyl methacrylate; (5) The homemade light diffuser and composite polymethyl methacrylate in the diffusion layer, the green light perovskite, composite homemade light diffuser and polymethyl methacrylate in the quantum dot layer are prepared according to the mass percentage ratio, and the diffusion layer sheet layer, quantum dot layer sheet layer and diffusion layer sheet layer are formed by in-mold co-extrusion molding. The extrusion speed is 2.8m / min to obtain a PP diffuser plate. Example 2

[0021] In this embodiment, the diffusion layer includes the following components in percentage by mass: 9% of a homemade light diffuser and the rest of the composite polymethyl methacrylate; the thickness of the diffusion layer is 6.0% of the thickness of the PMMA diffusion plate; In this embodiment, the quantum dot layer includes the following components in percentage by mass: 2.3% of green light perovskite, 3.5% of a homemade light diffuser, and the rest is polymethyl methacrylate; the green perovskite is a green quantum dot with a particle size of 2 nm; In this embodiment, the thickness of the PMMA diffuser plate is 1.7 mm, and the manufacturing method is as follows: (1) Mix sodium hydroxide, ethylene glycol and deionized water in equal amounts, stir evenly, add zinc nitrate 0.3 times the mass of sodium hydroxide and selenium powder 0.3 times the mass of sodium hydroxide, stir at 300 rpm for 60 min, transfer to a high-pressure reactor, seal the high-pressure reactor and place it in a drying oven at 180°C, keep warm for 22 h, cool to room temperature, wash with 50% ethanol solution 4 times, finally wash and dry at 65°C, anneal at 750°C for 4 h, grind to obtain nano zinc selenide; (2) Mix nano zinc selenide and 62% sulfuric acid in a mass ratio of 1.5:20, heat to 44°C, react at 600 rpm for 65 min, add an equal volume of deionized water and centrifuge, add 2-bromoisobutyryl bromide (3 times the mass of nano zinc selenide), triethylamine (5 times the mass of nano zinc selenide) and N,N-dimethylformamide (5 times the mass of nano zinc selenide), heat to 70°C, react for 24 h, then add cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine, the mass ratio of nano zinc selenide, cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine is 1:0.3:4:6:0.6:0.05, heat to 105°C, react for 24 h, and prepare a homemade light diffuser; (3) Methyl methacrylate, azobisisoheptanenitrile, sodium iodide and diethylene glycol dimethyl ether were mixed in a mass ratio of 10:0.4:0.152:11, stirred evenly, sealed, and frozen at -45°C for 10 hours. After vacuuming and natural thawing, the oxygen in the system was replaced with an argon flow and sealed, and transferred to an oil bath at 80°C. 0.15 times the mass of methyl methacrylate p-chloromethylstyrene was added, and after reacting for 7 hours, the mixture was dissolved in tetrahydrofuran and precipitated with anhydrous ethanol, and dried to obtain branched polymethyl methacrylate; (4) Xylene and branched polymethyl methacrylate were mixed in a mass ratio of 1:1.1, stirred evenly, and then heated to 80°C for 65 minutes, and then acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile were added, and the mass ratio of xylene, acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile was 1:0.55:0.55:0.3:0.02. The mixture was sealed and heated to 80°C, and the reaction was kept for 7 hours. The mixture was transferred to a rotary evaporator, heated in a boiling water bath and evacuated to obtain a composite polymethyl methacrylate; (5) The homemade light diffuser and composite polymethyl methacrylate in the diffusion layer, the green light perovskite, composite homemade light diffuser and polymethyl methacrylate in the quantum dot layer are prepared according to the mass percentage ratio, and the diffusion layer sheet layer, quantum dot layer sheet layer and diffusion layer sheet layer are formed by in-mold co-extrusion molding. The extrusion speed is 3.3m / min to obtain a PP diffuser plate. Example 3

[0022] In this embodiment, the diffusion layer includes the following components in percentage by mass: 12% of a homemade light diffuser and the rest of the composite polymethyl methacrylate; the thickness of the diffusion layer is 7.0% of the thickness of the PMMA diffusion plate; In this embodiment, the quantum dot layer includes the following components in percentage by mass: 4% green light perovskite, 5% homemade light diffuser, and the rest is polymethyl methacrylate; the green perovskite is a green quantum dot with a particle size of 3 nm; In this embodiment, the thickness of the PMMA diffuser plate is 1.8 mm, and the manufacturing method is as follows: (1) Mix sodium hydroxide, ethylene glycol and deionized water in equal amounts, stir evenly, add zinc nitrate 0.4 times the mass of sodium hydroxide and selenium powder 0.4 times the mass of sodium hydroxide, stir at 400 rpm for 70 min, transfer to a high-pressure reactor, seal the high-pressure reactor and place it in a drying oven at 190°C, keep warm for 24 h, cool to room temperature, wash with 60% ethanol solution 5 times, finally wash and dry at 70°C, anneal at 850°C for 5 h, grind to obtain nano zinc selenide; (2) Mix nano zinc selenide and 64% sulfuric acid in a mass ratio of 12:20, heat to 45°C, react at 800 rpm for 80 min, add an equal volume of deionized water and centrifuge, add 2-bromoisobutyryl bromide (4 times the mass of nano zinc selenide), triethylamine (6 times the mass of nano zinc selenide) and N,N-dimethylformamide (6 times the mass of nano zinc selenide), heat to 72°C, react for 24 h, then add cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine, the mass ratio of nano zinc selenide, cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine is 1:0.4:4:6:0.7:0.08, heat to 110°C, react for 24 h, and prepare a homemade light diffuser; (3) Methyl methacrylate, azobisisoheptanenitrile, sodium iodide and diethylene glycol dimethyl ether were mixed in a mass ratio of 10:0.4:0.2:12, stirred evenly, sealed, and frozen at -50°C for 12 hours, then vacuumed and thawed naturally, the oxygen in the system was replaced by an argon flow, and then sealed, transferred to an oil bath at 85°C, and p-chloromethylstyrene with a mass of 0.2 times that of methyl methacrylate was added. After reacting for 68 hours, the mixture was dissolved in tetrahydrofuran and precipitated with anhydrous ethanol, and dried to obtain branched polymethyl methacrylate; (4) Xylene and branched polymethyl methacrylate were mixed in a mass ratio of 1:1.2, stirred evenly, and then heated to 85°C for 80 minutes, and then acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile were added, and the mass ratio of xylene, acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile was 1:0.6:0.6:0.3:0.02. The mixture was sealed and heated to 85°C, and the reaction was kept at this temperature for 8 hours. The mixture was transferred to a rotary evaporator, heated in a boiling water bath and evacuated to obtain a composite polymethyl methacrylate; (5) The homemade light diffuser and composite polymethyl methacrylate in the diffusion layer, the green light perovskite, composite homemade light diffuser and polymethyl methacrylate in the quantum dot layer are prepared according to the mass percentage ratio, and the diffusion layer sheet layer, quantum dot layer sheet layer and diffusion layer sheet layer are formed by in-mold co-extrusion molding. The extrusion speed is 3.8 m / min to obtain a PP diffuser plate.

[0023] Comparative Example 1 The preparation method of comparative example 1 is the same as that of example 2. The difference between the PMMA diffusion plate and example 2 is that the self-made light diffuser is prepared by grafting polystyrene on the surface of zinc selenide.

[0024] Comparative Example 2 The preparation method of comparative example 2 is the same as that of example 2. The difference between the PMMA diffusion plate and example 2 is that the self-made light diffusing agent is only nano zinc selenide.

[0025] Comparative Example 3 The preparation method of Comparative Example 3 is the same as that of Example 2. The difference between the PMMA diffusion plate and Example 2 is that the diffusion layer includes a self-made light diffusing agent and polymethyl methacrylate.

[0026] Effect example Table 1 below shows the performance analysis results of the PMMA diffusion plates prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 3:

[0027] By comparing the experimental data of the examples and the comparative examples in Table 1, it can be clearly found that the PMMA diffusion plates prepared using Examples 1, 2, and 3 have excellent haze and transparency.

[0028] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, it can be found that the homemade light diffuser prepared by grafting polystyrene on the surface of nano-zinc selenide has a triangular morphology. Sulfate groups are introduced on the surface of the nano-zinc selenide, so that the surface of the nano-zinc selenide carries a large amount of negative charge, and polystyrene is grafted on the surface, so that the homemade light diffuser can be evenly dispersed in the composite polymethyl methacrylate for scattering, thereby effectively improving the high haze of the diffusion layer.

[0029] From the comparison of the experimental data of Example 1, Example 2, Example 3 and Comparative Example 3, it can be found that the composite polymethyl methacrylate includes polymethyl methacrylate and polymethyl methacrylate microspheres; the polymethyl methacrylate microspheres are prepared by crosslinking and precipitation polymerization of branched polymethyl methacrylate and polyacrylic acid. The polymethyl methacrylate is dissolved in xylene, and then the polymerization monomer acrylic acid, the crosslinking agent pentaerythritol triallyl ether, and the initiator azobisisobutyl cyanide are added, and the precipitation polymerization reaction is initiated by heating to prepare the polymethyl methacrylate composite microspheres. The polymethyl methacrylate microspheres are added to the polymethyl methacrylate, which can be scattered together with the homemade light diffuser, thereby further improving the high haze of the diffusion layer, while reducing the viscosity of the polymethyl methacrylate, increasing the fluidity, and ensuring the transparency of the PMMA diffusion plate.

[0030] Obviously, the above embodiments are merely examples for clearly illustrating the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. However, these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.

Claims

1. A PMMA diffuser plate, characterized in that: It includes two diffusion layers, an upper diffusion layer and a quantum dot layer in the middle; the diffusion layer includes the following components in mass percentage: 6-12% of a homemade light diffuser, and the rest is composite polymethyl methacrylate; the quantum dot layer includes the following components in mass percentage: 1-4% of green light perovskite, 1-5% of a homemade light diffuser, and the rest is polymethyl methacrylate; the green perovskite is a green quantum dot with a particle size of 2-3nm.

2. A PMMA diffuser plate according to claim 1, characterized in that: The self-made light diffuser is prepared by grafting polystyrene on the surface of nano zinc selenide.

3. A PMMA diffuser plate according to claim 2, characterized in that: The nano zinc selenide has a triangular shape and is prepared by the reaction of zinc nitrate, selenium powder, ethylene glycol and sodium hydroxide.

4. The PMMA diffuser plate according to claim 1, characterized in that: The composite polymethyl methacrylate comprises polymethyl methacrylate and polymethyl methacrylate microspheres; the polymethyl methacrylate microspheres are prepared by cross-linking and precipitation polymerization of branched polymethyl methacrylate and polyacrylic acid.

5. The PMMA diffuser plate according to claim 1, characterized in that: The thickness of the PMMA diffusion plate is 1.6-1.8 mm; the thickness of the diffusion layer is 5.0-7.0% of the thickness of the PMMA diffusion plate.

6. A method for manufacturing a PMMA diffuser plate as claimed in claim 1, characterized in that: The method comprises the following specific steps: preparing the self-made light diffuser and composite polymethyl methacrylate in the diffusion layer, the green light perovskite, the composite self-made light diffuser and polymethyl methacrylate in the quantum dot layer according to the mass percentage ratio, forming a diffusion layer sheet layer, a quantum dot layer sheet layer and a diffusion layer sheet layer which are sequentially laminated and composited together by in-mold co-extrusion molding, and the extrusion speed is 2.8-3.8 m / min to obtain a PP diffusion plate.

7. The method for manufacturing a PMMA diffuser plate according to claim 6, characterized in that: The preparation method of the self-made light diffuser is as follows: nano zinc selenide and sulfuric acid with a mass fraction of 60-64% are mixed in a mass ratio of 1-2:20, heated to 43-45° C., reacted at 400-800 rpm for 50-80 min, added with an equal volume of deionized water and centrifuged, 2-bromoisobutyryl bromide with a mass of 1-4 times that of the nano zinc selenide, triethylamine with a mass of 4-6 times that of the nano zinc selenide and N,N-dimethylformamide with a mass of 4-6 times that of the nano zinc selenide are added, heated to 68-72° C., reacted After 24 hours, cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine were added. The mass ratio of nano zinc selenide, cuprous bromide, anisole, styrene, ethyl bromoisobutyrate and N,N,N',N',N''-pentamethyldiethylenetriamine was 1:0.2~0.4:4:6:0.5~0.7:0.02~0.

08. The temperature was raised to 100~110℃ and the reaction was carried out for 24 hours to obtain a homemade light diffuser.

8. The method for manufacturing a PMMA diffuser plate according to claim 7, characterized in that: The preparation method of the nano zinc selenide comprises the following steps: mixing sodium hydroxide, ethylene glycol and deionized water in equal amounts, stirring evenly, adding zinc nitrate in an amount of 0.2 to 0.4 times the amount of the sodium hydroxide and selenium powder in an amount of 0.2 to 0.4 times the amount of the sodium hydroxide, stirring at 200 to 400 rpm for reaction for 50 to 70 minutes, transferring the mixture to a high-pressure reactor, sealing the high-pressure reactor and placing it in a drying oven at 170 to 190° C., keeping the temperature for 20 to 24 hours, cooling the mixture to room temperature, washing the mixture 3 to 5 times with an ethanol solution having a mass fraction of 40 to 60%, finally washing and drying the mixture at 60 to 70° C., and finally annealing the mixture at a temperature of 650 to 850° C. for 3 to 5 hours, and grinding the mixture to obtain the nano zinc selenide.

9. The method for manufacturing a PMMA diffuser plate according to claim 6, characterized in that: The preparation method of the composite polymethyl methacrylate comprises the following steps: mixing xylene and branched polymethyl methacrylate in a mass ratio of 1:1-1.2, stirring evenly, heating to 75-85°C, and keeping the temperature for 50-80 minutes, adding acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile, wherein the mass ratio of xylene, acrylic acid, pentaerythritol triallyl ether and azobisisobutyronitrile is 1:0.5-0.6:0.5-0.6:0.3:0.02, sealing and heating to 75-85°C, keeping the temperature for reaction for 5-8 hours, transferring to a rotary evaporator, heating in a boiling water bath and evacuating to obtain the composite polymethyl methacrylate.

10. The method for manufacturing a PMMA diffuser plate according to claim 9, characterized in that: The preparation method of the branched polymethyl methacrylate comprises the following steps: methyl methacrylate, azobisisoheptanenitrile, sodium iodide and diethylene glycol dimethyl ether are mixed in a mass ratio of 10:0.4:0.1-0.2:10-12, stirred evenly, sealed, frozen at -40--50°C for 8-12h, vacuumed, thawed naturally, replaced oxygen in the system with an argon flow, sealed, transferred to an oil bath pot at 75-85°C, added with 0.1-0.2 times the mass of methyl methacrylate p-chloromethylstyrene, reacted for 6-8h, dissolved with tetrahydrofuran, precipitated with anhydrous ethanol, and dried to obtain the branched polymethyl methacrylate.

Citation Information

Patent Citations

  • Perovskite / polymer composite luminescent material and preparation method thereof

    CN104861958A

  • Quantum dot diffusion plate and preparation method thereof

    CN114895492A